Major advances in understanding and prediction of tropical cyclones over north Indian Ocean : A Perspective
lkj & mRrjh fgUn egklkxj esa m".kdfVca/kh pØokrksa ij fd, x, vuqla/kku xr 150 o"kksZa esa fofHkUu pj.kksa ls xqtjs gSa vkSj vf/kd rFkk csgrj izsk.kksa dks fodflr djus ds fy, izkS|ksfxdh ds :Ik es bldk fodkl fd;k x;k gSA 20oha ’krkCnh ds e/; rd leqnz esa bl vkinkdkjh ifj?kVuk ds cuus vkSj blds rhoz gksus dh tkudkjh iksrksa esa gh dqN gn rd fojyrk ls izkIr gksus okys izsk.kksa ds ek/;e ls feyrh Fkh vkSj blfy, 1960 ds n’kd rd Hkkjr esa fd, x, vf/kdka’k vuqla/kku v/;;uksa esa pØokrksa ds tyok;q foKku] mudh /kjkryh; lajpuk] mudh xfr vkSj leqnz esa tgktksa dks ig¡qpkusa okyh kfr dks vuns[kk djus okys fu;eksa ij vf/kd cy fn;k x;k FkkA ekSle jsMkj] mifjru ok;q ifjKkiuksa] vuqla/kku ok;q;ku losZk.k ekSle mixzgksa vkSj daI;wVjksa ds ek/;e ls izkIr dh xbZ ubZ ok;qeaMyh; izks|ksfxdh ds izLrqrhdj.k ls 1950 ds n’kd ls ysdj 1980 ds n’kd ds nkSjku fofHkUu ns’kksa ds m".kdfVca/kh pØokr vuqla/kku esa vk’p;Ztud :Ik ls ifjorZu vk;k gSA bl vof/k esa m".kdfVca/kh pØokrksa ds laiw.kZ mRifRr pØ dk izfr:i.k djus ds fy, lS)kafrd v/;;uksa vkSj daI;wVj fun’kksaZ ds fodkl esa lq/kkj ns[kk x;k gSA bl vof/k esa m".kdfVca/kh pØokr ds ekxZ dk iwokZuqeku yxkuk Hkh vuqla/kku dk ,d ks= cu x;k gS vkSj 1950 ds n’kd ls ysdj 1980 ds n’kd ds nkSjku tyok;q foKku] flukfIVd lkaf[;dh; vkSj xfrdh; i)fr;ksa ij vk/kkfjr rduhdksa ds izdkjksa esa fujarj fodkl gqvk gS rFkk bUgsa ekU;rk feyh gSA xr 10 o"kksZa dh vof/k ds nkSjku fodflr ns’kksa esa HkweaMyh; ifjpkyu fun’kksZa esa fufgr ifj"Ñr mPp foHksnu ds fun’kksZa dk fodkl fd;k x;k gS vkSj ikjLifjd fØ;kvksa dh izfØ;k ds :Ik esa bl Ik)fr dk fodkl djus vkSj bldh xfr dk iwokZuqeku yxkus ds fy, budh tk¡p dh xbZ gSA ;s iw.kZ :i ls lgh ikbZ xbZ gSaA Hkkjr esa Hkh bl izdkj ds fodklksa dks viuk;k x;k gSA bl ’kks/k&i= esa m".kdfVca/kh pØokr ds fodkl vkSj bldh xfr esa lfUufgr izR;k izfØ;kvksa ds laca/k esa fd, x, izeq[k fodklksa dh lwph miyC/k djkus dk iz;kl fd;k x;k gSA lkekU; :Ik ls HkweaMyh; vuqla/kku ds ks= esa fd, x, iz;kl fgan egklkxj csflu esa fd, tk jgs v/;;uksa ij dsafnzr jgs gSaA mRrjh fgan egklkxj esa m".kdfVca/kh pØokrksa ds vUr% nl o"khZ; fHkUurkvksa dh tk¡p dh xbZ gS vkSj 1980 ds n’kd ls budh xfr;ksa esa vDlj vR;kf/kd deh ns[kh xbZ gSA fgan egklkxj csflu esa m".k@’khr bulksa dh ?kVukvksa ds e/; dksbZ laca/k ugha ik;k x;k gSA izpaM m".kdfVca/kh pØokrksa ds fodkl vkSj xfr ds fy, vko’;d o`gr eku fLFkfr;ksa dh izÑfr ls lacaf/kr izsk.kkRed vkSj lSkafrd ekWMfyax i)fr;ksa esa daI;wVj izfr:i.kksa lfgr izsk.kkRed vkSj lS)kafrd i)fr;ksa ls fHkUu fHkUu fopkjksa dk irk pyk gSA mRrjh fgan egklkxj csflu esa fd, x, vkSj vf/kd vuqla/kku dh vksj fo’ks"k /;ku nsus dh fn’kk esa dqN lq>ko fn, x, gSaA Research on tropical cyclones in the north Indian Ocean has passed through different phases in the last 150 years and progress was made as the technology for more and better observations evolved. Till the middle of the 20th century, the only way of knowing about the formation and intensification of this disastrous phenomenon, while out at sea, was through rather sparse ship observations and hence the climatology of the cyclones, their surface structure, movement and the rules to avoid the damage to shipping at sea were emphasized in most of the research studies in India till 1960s. Introduction of new atmospheric technologies through weather radars, upper air soundings, weather satellites and computers have brought a phenomenal change in tropical cyclone research in different countries during 1950s to 1980s. The period also witnessed break-through in theoretical studies and the development of computer models to simulate the complete genesis cycle of tropical cyclones. Predicting the track of tropical cyclone also became an area of active research in this period and a variety of techniques were increasingly developed. During the last 10 years sophisticated high resolution models embedded within global circulation models have been developed in advanced countries and tested for predicting the development and movement of the system as an interactive process. In India, too such developments have been adopted. Within the scope of global research effort in general, the focus of the article is on the studies in north Indian Ocean basin. Inter-decadal variation of tropical cyclones in the north Indian Ocean has been examined and the frequency of their formations have shown drastic decrease since 1980s. No connection is found between the warm/cold ENSO events in the Indian Ocean basin and tropical cyclone frequency in the basin. Observational and theoretical approaches with computer simulations have brought a convergence of views concerning the nature of large-scale conditions needed for development and movement of severe tropical cyclones. Some suggestions are provided for directing special attention toward further research in this area in the north Indian Ocean basin. , number=1, journal=MAUSAM, author=SIKKA, D. R., year=2006, month=Jan., pages=165–196